1980
DOI: 10.1007/bf02374036
|View full text |Cite
|
Sign up to set email alerts
|

Sexual maturation and seasonal changes in reproductive phenomena of male Japanese monkeys (Macaca fuscata) at Takasakiyama

Abstract: ABSTRACT. The authors examined testis tissues and blood which were collected from free-ranging Japanese monkeys of the Takasakiyama troop during four periods in 1971 (mating season: late January-early February; early birth season: June; late birth season: August; and intermediate season between birth season and mating season: October), and studied their sexual maturation and seasonal changes in reproductive phenomena.Results of observations on the testis and plasma testosterone concentration were in agreement … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
31
2
1

Year Published

1983
1983
2003
2003

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 67 publications
(37 citation statements)
references
References 12 publications
3
31
2
1
Order By: Relevance
“…The timing of major physiological growth events, such as weaning and sexual maturation, were the same for the two groups, and similar to those reported previously in Japanese macaques [8,[10][11][12]. Trends of growth in the Enclosure group macaques were similar to those of free-ranging Japanese macaques [3,4].…”
Section: Resultssupporting
confidence: 83%
“…The timing of major physiological growth events, such as weaning and sexual maturation, were the same for the two groups, and similar to those reported previously in Japanese macaques [8,[10][11][12]. Trends of growth in the Enclosure group macaques were similar to those of free-ranging Japanese macaques [3,4].…”
Section: Resultssupporting
confidence: 83%
“…As Japanese macaques are strictly seasonal breeders [18][19][20][21][22], seasonal changes in hormone secretion would be superimposed on the agedependent changes. The present study, therefore, attempted to obtain seasonal and age-dependent components from the hormonal and body weight changes around the adolescent period.…”
Section: Discussionmentioning
confidence: 99%
“…This reproductive seasonality would presumably affect the timing of sexual maturation [20] as well as body growth. Our previous study on the morphological growth of the Japanese macaque by the long-term longitudinal method demonstrated that its adolescent growth is characterized by slowness and late start, resulting from adaptation to highly seasonal environment in a temperate zone [23].…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The process of sexual maturation has been well studied, especially in Japanese macaques (Nigi, 1975;Nigi et al, 1980;Matsubayashi and Mochizuki, 1982). There are many reports on the histological structure of the male reproductive organ as well as their seasonal changes (Kinzey, 1971;Glick, 1979).…”
Section: Discussionmentioning
confidence: 99%